La infodemia. Caso México 2020-2021 - Ambriz Guillén, Víctor Alejandro (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
The saturation of information on social networks, about the COVID-19 pandemic, has reflected the deterioration of communication strategies by the Mexican Government, generating with this the lack of compliance with the standards of truthful and timely communication, this, by disseminating discursive information dissonances that lead vulnerable educational sectors to confrontations and acts of violence, a product of digital misinformation and the infodemic.

La saturación de información en redes sociales, sobre la pandemia COVID- 19, ha reflejado el deterioro de estrategias de comunicación por parte del Gobierno mexicano, generando con esto la falta de cumplimiento de los estándares de una comunicación veraz y oportuna, esto, al difundir disonancias discursivas de información que llevan a los sectores de vulnerabilidad educativa a confrontaciones y actos de violencia, producto de la desinformación digital y la infodemia.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho de la Información
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2022-0908; Desinformación; Redes sociales; Responsabilidad informativa; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/8445